1x-5-6x=7-8x+3

Simple and best practice solution for 1x-5-6x=7-8x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1x-5-6x=7-8x+3 equation:


1x-5-6x=7-8x+3

We simplify the equation to the form, which is simple to understand
1x-5-6x=7-8x+3

We move all terms containing x to the left and all other terms to the right.
+1x-6x+8x=+7+3+5

We simplify left and right side of the equation.
+3x=+15

We divide both sides of the equation by 3 to get x.
x=5

See similar equations:

| (x)=3x^2-5x+11 | | 16d/16d | | 21+5(5x+3)=19x-2(7x-3) | | m+17= | | 6A+8b+8a-7+5b= | | 4x^3+8x^2+x+1=6.5 | | -3v+15=6(v+4) | | 5x+7=9x-24 | | 8X-4p-5x= | | 8x-12=5x+25 | | 8.1(4.6)= | | 2x+19=9x+6 | | 2x-3+6x-8=5x+4 | | 4/5=9/10 | | 5v-4.2=8.3 | | p-(17)=-23 | | -11x=-6 | | 2x^2=0.08 | | -5/8=3/4=5/8 | | 59=-x/8 | | 4x=a-6 | | 15(x)+85(y)=2556 | | 3(1+-1y)=8+(-5y) | | x^3-6x^2-15x+40=0 | | -5=-27w | | -w/9=-50 | | -2w+5(w-2)=-19 | | -39=3(v+3)+5v | | 9x+4y=10 | | 1/4x1/4x1/4x1/4 | | 3m-12=3(8m+3) | | 8m^2+72m-16=0 |

Equations solver categories